PENGARUH GAYA MENGAJAR GURU TERHADAP SELF-EFFICACY PADA PESERTA DIDIK KELAS V - Arifin, Nurdin; Yulianti, Maria Agnestis (SISTEMA: Jurnal Pendidikan, 2023)
In the process of learning, several indicators affect self-efficacy in the learning process namely the concept of teaching, kinds of teaching, types of teaching styles, and variations in teacher teaching styles. Self-efficacy is to measure success in the implementation of learning. Self-efficacy is influenced by several indicators, such as factors that influence self-efficacy and self-efficacy classification. The purpose of this study is to find out if there was an influence of teacher teaching style on self-efficacy in students grade V at SDN 006 Samarida Ulu academic year 2022/2023. The techniques sampling used was saturated sampling techniques. The subjects were 66 students. Data collection techniques was obtained by spreading the questionnaire and retrieving documentation. Data analysis techniques used statistical analysis using IBM SPSS 21. The hypothetical test results concluded that the result of the meaningful test was obtained by 8,463 > by 3.99, so it could be concluded that there was an influence on the teacher teaching style variable (X) towards self-efficacy (Y) was Ha. The effect was determined by a correlation coefficient of r2 determination of 0.116 or 11.6%.